Masih Pentingkah UN bagi Siswa? Is UN Still Important for Students? - Lestari, Suci Paramitha; Safari, NFN (Pusat Asesmen dan Pembelajaran, 2019)
The main purpose of this study is to answer the following question. Is there any influence of junior high school student’s opinion on the importance of the National Examination against the 2018 National Examination results because currently the National Examination is no longer a determinant of graduation? The population of this study was junior high school students participated in the National Examination in 2018. The data in this study were in the form of test scores and students’ answers to questionnaires in 34 provinces throughout Indonesia. Filling out questionnaires was carried out voluntarily on the last day of the National Examination, so the number of respondents filling out the questionnaire was 3.224.331 from 37.859 junior high school students. The number of respondents is the sample in this study. Based on the results of the t-test analysis obtained as follows. The influence of student opinions stating that the UN is important and not important to the 2018 UN results even though the UN is not a determinant of graduation is proven. This means that there is a significant influence (P <0,000) of the student's opinions towards the 2018 National Examination results for subjects: Indonesian, English, Mathematics, and Science, (Sig. 0,000). Most of the SMP / MTs students amount to 199.222 (90.7%) stated that the National Examination was important, while students who stated that the UN was not important were 20.340 (9.3%) students. The conclusion is that there is an influence of the junior high school students’ opinion about the importance of the National Examination towards the 2018 UN results even though the National Examination is not a determinant of graduation.